Relationship between personality type and musculoskeletal disorders among office staff - Baberi, Fatemeh; Jahandideh, Zahra; Akbari, Mojtaba; Shakerian, Mahnaz; Choobineh, Alireza (La Medicina del Lavoro, 2019)
Background: Musculoskeletal disorders (MSDs) have been recognized as common health-related problems in the workplace. Accordingly, poorly-designed workstations and assigned tasks can lead to exposure to risk factors inducing MSDs among office staff. Accompanied by physical risk factors, psychological ones in working environments can also contribute to MSDs occurrence. Thus, the purpose of this study was to examine the relationship between personality types as a psychological factor and MSDs occurrence among office staff. Methods: This cross-sectional study was carried out on office staff working at Shiraz University of Medical Sciences (SUMS) in 2016. The participants included 339 employees recruited using multi-stage simple random sampling method. The required data were likewise collected via a demographic characteristics information checklist, the Personality Pattern Questionnaire (PPQ), as well as the standardized Nordic Musculoskeletal Questionnaire (NMQ). Results: The findings revealed that the participants’ mean±standard deviation (SD) age were 36.4±7.8 years. As well, the most prevalent MSDs complaints were reported in lower back, knee, and neck regions with relative frequencies of 35%, 30%, and 25% respectively. Moreover, the results demonstrated that 0.6% of the participants were determined as individuals having a strong tendency for type A personality, 26.8% of them showed tendency for type A personality, 63.1% of these employees were categorized into those having a tendency for type B personality, and 9.4% of them were identified as participants who showed a strong tendency for type B personality. Additionally, statistically significant relationships were observed between personality types and MSDs occurrence (p=0.023). Furthermore, musculoskeletal symptoms were reported more prevalent among individuals having tendency for type A personality. Conclusion: Personality types and MSDs occurrence seemed to be associated. It was thus suggested to take account of psychological factors (e.g., personality types) in macro policy-making, employee selection, and professional staff training programs.